2014
DOI: 10.1186/s12863-014-0119-2
|View full text |Cite
|
Sign up to set email alerts
|

Promoter polymorphisms in genes involved in porcine myogenesis influence their transcriptional activity

Abstract: BackgroundSuccess of meat production and selection for improvement of meat quality is among the primary aims in animal production. Meat quality traits are economically important in swine; however, the underlying genetic nature is very complex. Therefore, an improved pork production strongly depends on identifying and studying how genetic variations contribute to modulate gene expression. Promoters are key regions in gene modulation as they harbour several binding motifs to transcription regulatory factors. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Polymorphisms in the 5’ regulatory region of a gene could affect its transcriptional activity [36]. In the present study, luciferase reporter constructs with the GG genotype of rs321936011 had a lower promoter activity of the MAOA gene than that of AA genotypes.…”
Section: Discussionmentioning
confidence: 45%
“…Polymorphisms in the 5’ regulatory region of a gene could affect its transcriptional activity [36]. In the present study, luciferase reporter constructs with the GG genotype of rs321936011 had a lower promoter activity of the MAOA gene than that of AA genotypes.…”
Section: Discussionmentioning
confidence: 45%
“…In addition, the cumulative protective effect depends on the number of genotypes, and the risk of recurrent abortion is significantly reduced with increases in the number of observed genotypes. Promoter polymorphisms might have important functions in regulating the expression of mature lncRNAs and some transcription factors (Bongiorni et al, 2014). However, Wang et al found that rs1041279 in the HULC gene is associated with increased risk for hepatocellular cancer and suggested that this polymorphism might be a biomarker for hepatocellular cancer risk (Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…; Bongiorni et al . ). Thus, the identification of three linked SNPs ( ASGA0040372 , RS346215414 and RS331766122) located at the start of the pig GPAT3 gene implies that the regulatory region of GPAT3 may play an important role in pig growth rate.…”
Section: Associations Of the Five Snps In The Gpat3 Gene With The Fivmentioning
confidence: 97%